KAVITAS PARU DENGAN PENYEBAB INFEKSI - Setianingrum, Findra; Nandipinto, Finny; Rozaliyani, Anna (Universitas Muhammadiyah Surabaya, 2026)
Pulmonary cavities are an important radiological finding in various infectious and non‑infectious diseases.​ Infection‑related cavities are usually associated with tuberculosis (TB), non‑tuberculous mycobacterial (NTM) infection, chronic pulmonary aspergillosis, and echinococcosis, each with distinct mechanisms of formation and radiologic patterns.​ In TB and NTM, tissue necrosis and bronchiectasis lead to the formation of cavitary spaces that serve as reservoirs for organisms with a high burden and facilitate transmission.​ Residual cavities may then undergo secondary colonization by Aspergillus spp, resulting in a spectrum of chronic pulmonary aspergillosis with findings such as aspergilloma and thick‑walled cavities.​ Echinococcus forms cysts that, when ruptured, can appear as cavitary lesions with the “water lily” sign, adding yet another differential diagnosis for pulmonary cavities.​ Understanding radiologic patterns, pathogenesis, and microbiological correlations can be used as an important clue to distinguish etiologies and to select appropriate management for patients.